2011
DOI: 10.1103/physrevb.84.094456
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced exchange and reduced magnetization of Gd in an Fe/Gd/Fe trilayer

Abstract: The exchange interaction of Gd adjacent to Fe has been characterized by transport measurements on a double spin valve with a Fe/Gd/Fe trilayer as the middle layer. Our measurements show that the ferromagnetism of the Gd is enhanced by the presence of the Fe, and it remains ferromagnetic over its Curie temperature up to a thickness no smaller than 1 nm adjacent to the Fe. This thickness is more than double what has been reported before. Additionally, the saturation magnetization of the thin Gd layer sandwiched … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
5
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 23 publications
(37 reference statements)
5
5
0
Order By: Relevance
“…The reduction of layer magne tization is usually at most 20-30%. A similar strong decrease in the magnetization was detected in [28] for the Fe/Gd/Fe system: it was found that ≈ 1545 G and ≈ 1030 G. A more than twofold decrease in the magnetization of thin Gd layers as compared to the tab ulated value was also detected for the Gd/Cr multilayer system [29]. The suppression of the magnetization of Gd in the Gd/Cr/FeCo system in [20] was related to the presence of a paramagnetic crystalline fcc phase, which is nonequilibrium in bulk gadolinium.…”
Section: Static Magnetization Measurementssupporting
confidence: 75%
“…The reduction of layer magne tization is usually at most 20-30%. A similar strong decrease in the magnetization was detected in [28] for the Fe/Gd/Fe system: it was found that ≈ 1545 G and ≈ 1030 G. A more than twofold decrease in the magnetization of thin Gd layers as compared to the tab ulated value was also detected for the Gd/Cr multilayer system [29]. The suppression of the magnetization of Gd in the Gd/Cr/FeCo system in [20] was related to the presence of a paramagnetic crystalline fcc phase, which is nonequilibrium in bulk gadolinium.…”
Section: Static Magnetization Measurementssupporting
confidence: 75%
“…Thus, the most probable reason for the observed strong reduction of magnetization seems to be due to a large degree of structural disorder and amorphousness of the grown FM layers. Indeed, such effects were previously reported for both thin polycrystalline Gd [27,28] and amorphous Fe layers [29]. In both cases the magnetization reduction can reach ∼ 50% of its bulk value.…”
Section: Magnetization Dynamicssupporting
confidence: 55%
“…At room temperature, bulk Gd is paramagnetic because of its low Curie temperature (292 K). Nevertheless, one has to notice that stabilization of ferromagnetism in Gd for temperature up to 350 K has already been reported and explained by the exchange coupling at the interface with Co [10][11]. In our case, Fig.…”
supporting
confidence: 53%
“…Indeed, the properties of RE/TM multilayers have been widely studied in the past [4][5][9][10][11] but the influence of heat treatment on the magnetic behavior of multilayers has not been enough researched. It has also been shown that interfacial magnetic disorder [12] impacts the magnetism and affects to the magnetization reversal processes [13].…”
mentioning
confidence: 99%